Cardiogenic shock among cancer patients - Curtiaud, Anais; Delmas, Clement; Gantzer, Justine; Zafrani, Lara; Siegemund, Martin; Meziani, Ferhat; Merdji, Hamid (Frontiers in Cardiovascular Medicine, 2022)
Sophisticated cancer treatments, cardiovascular risk factors, and aging trigger acute cardiovascular diseases in an increasing number of cancer patients. Among acute cardiovascular diseases, cancer treatment, as well as the cancer disease itself, may induce a cardiogenic shock. Although increasing, these cardiogenic shocks are still relatively limited, and their management is a matter of debate in cancer patients. Etiologies that cause cardiogenic shock are slightly different from those of non-cancer patients, and management has some specific features always requiring a multidisciplinary approach. Recent guidelines and extensive data from the scientific literature can provide useful guidance for the management of these critical patients. Even if no etiologic therapy is available, maximal intensive supportive measures can often be justified, as most of these cardiogenic shocks are potentially reversible. In this review, we address the major etiologies that can lead to cardiogenic shock in cancer patients and discuss issues related to its management.